FORMULATION AND CHARACTERIZATION OF FLOATING TABLET DOSAGE FORM OF DUAL DELIVERY OF DRUG CURCUMIN AND BERBERINE HYDROCHLORIDE USING SIMULTANEOUS ESTIMATION BY UV SPECTROSCOPY - MAJUMDER, KOLLOL KUMAR; KUMAR, MANISH; PAHWA, RAKESH; LAMBA, AVNEET KAUR; SHANKAR, RAVI; TIWARI, ABHISHEK; TIWARI, VARSHA; RISHABH (International Journal of Applied Pharmaceutics, 2021)
Objective: The present study was aimed to develop a combinational floating tablet of curcumin and berberine HCl utilizing synthetic polymers synthetic HPMC K-15M and evaluate its various characteristics. Methods: The formulations were developed by the process of wet granulation and evaluated for drug content, content uniformity, floating lag time, total floating time, in vitro buoyancy studies, and in vitro drug release profile. A simultaneous estimation method for curcumin and berberine was developed using U. V spectroscopy. Results: The results clearly indicated that the tablets produced were having acceptable physical parameters. The absence of any drug/polymer/excipient interactions was confirmed using infrared spectroscopy. It was found that the drug content of was in between 96.22 to 99.45 % in all the formulations. Because of their low densities, in vitro floatability tests showed that most of the tablets floated for more than 8 h. The in vitro release studies confirmed the sustained release of more than 80 percent of drug contained within a period of 8 h. In vitro buoyancy was good in all three batches (F1-F3). The overall floating time for the F2 formulation was 24 h. After one month of storage at 40 °C and 75 percent RH, the F2 formulation showed no noticeable change in physical as well as pharmaceutical performance characteristics. Conclusion: Floating tablets of curcumin and berberine was successfully developed and had passed on various pharmaceutical parameters.